Effectiveness of Multimedia Courseware Based Instruction on Senior School Students’ Retention in Linear Equation Word Problems - Ridwan Enuwa Mohammed; Khadijat Saka Ameen; Ayuba Bala (International Journal of Educational Innovation and Research, 2023)
The increasing popularity of Multimedia courseware in education aims to address the challenges posed by abstract concepts and the consequent underachievement of students. It is also relevant to consider the limitations of working memory resources during multimedia courseware based instruction of abstract concepts in order to evaluate irrelevant factors that create unwanted cognitive drain and make retention difficult. The study investigated the effects of multimedia courseware based instruction on senior school students’ achievement and retention in linear equation word problems in Mathematics. The study adopted a quasi-experimental research design. In Gombe State Nigeria, 120 students (69 males and 51 females) were selected from three co-educational senior schools allocated either into experimental group or a control group. The results of the study indicated that students exposed to multimedia courseware based instruction achieved and retained linear equation word problems than their counterparts who were exposed to conventional teaching method. There was significant difference between the mean retention scores of male and female students exposed to multimedia courseware based instructions which the result is in favor of female students. High, medium and low achievers’ students exposed to multimedia courseware based instructions retained the concept of linear equations involving word problems and high scorer retained better. Based on the above findings it was recommended that multimedia courseware based instruction should be used in teaching and learning of Mathematics as it was found capable of improving students’ retention in linear equation word problems in Mathematics.